2017
DOI: 10.3748/wjg.v23.i48.8626
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium’s link to colorectal neoplasia sequenced: A systematic review and future insights

Abstract: AIMTo critically evaluate previous scientific evidence on Fusobacterium’s role in colorectal neoplasia development.METHODSTwo independent investigators systematically reviewed all original scientific articles published between January, 2000, and July, 2017, using PubMed, EMBASE, and MEDLINE. A total of 355 articles were screened at the abstract level. Of these, only original scientific human, animal, and in vitro studies investigating Fusobacterium and its relationship with colorectal cancer (CRC) were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 114 publications
2
59
0
Order By: Relevance
“…31 The latter has also been proposed as an etiological agent in colorectal cancer. [34][35][36][37][38] F nucleatum and Fusobacterium necrophorum have been implicated in acute appendicitis, 39 with an inverse relationship between previous appendectomy and the incidence of UC reported. 40 Prevotella species dominance (specifically P copri) was a prominent feature in many patients during and after FMT therapy, often associated with decreased Bacteroides in the enteric microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…31 The latter has also been proposed as an etiological agent in colorectal cancer. [34][35][36][37][38] F nucleatum and Fusobacterium necrophorum have been implicated in acute appendicitis, 39 with an inverse relationship between previous appendectomy and the incidence of UC reported. 40 Prevotella species dominance (specifically P copri) was a prominent feature in many patients during and after FMT therapy, often associated with decreased Bacteroides in the enteric microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Some bacterial species seem particularly prone to favoring colorectal cancer development. In this context, several studies have suggested a positive association between Fusobacterium and, particularly, Fusobacterium nucleatum and colorectal cancer development [ 507 ]. Even stronger associations were observed in colorectal cancers proximal to the splenic flexure and CIMP-high colorectal cancers [ 507 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several studies have suggested a positive association between Fusobacterium and, particularly, Fusobacterium nucleatum and colorectal cancer development [ 507 ]. Even stronger associations were observed in colorectal cancers proximal to the splenic flexure and CIMP-high colorectal cancers [ 507 ]. Additional data also suggested shorter overall survival in patients with increased Fusobacterium nucleatum DNA in the tumoral tissue [ 507 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported an overabundance of Fusobacterium nucleatum (F. nucleatum) in stool and tumor tissue of patients with colorectal cancer (1,2). Although mechanistic studies suggest an etiologic role of the bacterium in colorectal carcinogenesis, it remains possible that it is simply an opportunistic passenger within developing tumors (1).…”
Section: Introductionmentioning
confidence: 99%